Information‐based ranking of 10 compartment models of diffusion‐weighted signal attenuation in fixed prostate tissue. (21st March 2016) - Liang, Sisi; Panagiotaki, Eleftheria; Bongers, Andre; Shi, Peng; Sved, Paul; Watson, Geoffrey; Bourne, Roger
Abstract: This study compares the theoretical information content of single‐ and multi‐compartment models of diffusion‐weighted signal attenuation in prostate tissue. Diffusion‐weighted imaging (DWI) was performed at 9.4 T with multiple diffusion times and an extended range of b values in four whole formalin‐fixed prostates. Ten models, including different combinations of isotropic, anisotropic and restricted components, were tested. Models were ranked using the Akaike information criterion. In all four prostates, two‐component models, comprising an anisotropic Gaussian component and an isotropic restricted component, ranked highest in the majority of voxels. Single‐component models, whether isotropic (apparent diffusion coefficient, ADC) or anisotropic (diffusion tensor imaging, DTI), consistently ranked lower than multi‐component models. Model ranking trends were independent of voxel size and maximum b value in the range tested (1.6–16 mm 3 and 3000–10 000 s/mm 2 ). This study characterizes the two major water components previously identified by biexponential models and shows that models incorporating both anisotropic and restricted components provide more information‐rich descriptions of DWI signals in prostate tissue than single‐ or multi‐component anisotropic models and models that do not account for restricted diffusion. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In all four prostates either the Zeppelin‐sphere or Tensor‐sphere model was ranked highest in the large majority of voxels. The results suggest that both anisotropic and restricted components are required to accurately describe DWI signals measured over an extended range of b values and multiple diffusion times.